The peripheral blood inflammatory patterns in the control levels of asthma in children. (4th March 2021) - Coşkun, Orhan; Ercan, Nazli; Bostanci, Ilknur
Abstract: Objective: Asthma is the most common chronic inflammatory disease of childhood, but there are no useful and easily accessible laboratory tests routinely used in the diagnosis and follow-up of this disease in children. Therefore, this study aimed to investigate the roles of white blood cell (WBC) count, platelet count, mean platelet volume (MPV), and eosinophil percentage as full blood count inflammatory markers in evaluating the control level and follow-up of asthma in the pediatric age group. Methods: A retrospective review of patient records and files of 3, 580 patients diagnosed with asthma at the University of Health Sciences in Ankara, Turkey was performed. Patients who met inclusion/exclusion criteria were divided into two groups based on the asthma control level: controlled and uncontrolled. Laboratory data were compared according to the asthma control levels, drug use status, and atopy status of the patients. Results: A total of 348 patients between 4 and 18 years of age, who were followed-up with the diagnosis of asthma, were included in this study. A significant difference was found between the controlled and uncontrolled groups of asthma patients in terms of the eosinophil percentage (mean ± SD, respectively; 3.493 ± 2.24; 4.992 ± 3.43; p  = .003). When patients were grouped according to their asthma control levels and atopy status, only the eosinophil percentages were different in the logistic regression analysis (odds ratio = 1.276, 95% confidence interval = 1.113–1.462). Conclusion: Our study showed that the percentage of eosinophils can be used as an asthma control parameter, but additional prospective studies would be desirable to confirm our results.